A new species of the hermit crab genus Alainopaguroides McLaughlin, 1997 (Crustacea: Decapoda: Anomura: Paguridae) from the South China Sea - Han, Yuan-Yuan; Komai, Tomoyuki; Sha, Zhong-Li (Zootaxa, 2016)
A new species of the pagurid hermit crab, Alainopaguroides sinensis sp. nov., is described and illustrated on the basis of a single ovigerous female specimen collected from the South China Sea. It is immediately distinguished from other known congeneric species by the possession of a subdistal spine on the lateral margin of the basal segment of the antennular peduncle, although the most similar congener is A. andamanensis McLauglin, 2002. This is the first record of the genus from the South China Sea. An identification key to the species of the genus Alainopaguroides McLaughlin, 1997 is provided.